The curricular organization in alternation on the teacher's training courses: PRONERA and graduation Degree in Rural Education - Dulcinéa Campos; Dalva Mendes de França; Valmere Santana (Universidade Federal do Norte do Tocantins, 2019)
This article aims to contribute with reflections about the theoretical-methodological principles that guide the alternating curricular organization in Degree Rural Education courses. It also discuss how these precepts, materialized in the pedagogical work of the alternating course, can serve as a parameter for the construction of a new school reference. Based on a bibliographical research, supported by the conception of Rural Education, dated at the National Seminar of 2002 is made a analysis is based on the assumptions of dialectical historical materialism. In addition, it bases reflections about theoretical support of Moisey Mikhaylovich Pistrak, a Russian pedagogue who defended teacher training focused on the praxis, aiming at the development of teaching autonomy in the process of construction and reconstruction of practices and methods of education. The results of this study indicate that the proposal for an alternating curriculum organization in the Rural Education Degree, aimed at teaching coherent with the dialectical method of reality interpretation, gives teachers the necessary tools to rethink and transform the existing configuration of the rural school.